2015
DOI: 10.1016/j.jvs.2015.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Eph-B4 Mediates Vein Graft Adaptation By Regulation of eNOS

Abstract: Objectives-Vein graft adaptation is characterized by loss of expression of the tyrosine kinase receptor Eph-B4, the embryonic determinant of venous identity, without increased expression of its ligand Ephrin-B2, the embryonic determinant of arterial identity. eNOS is an important mediator of vessel remodeling. We hypothesized that the mechanism of action of Eph-B4 during vein graft adaptation might be via regulation of downstream eNOS activity. Methods-Mouse lung endothelial cells (MLEC)were stimulated with Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We have shown that eNOS is likely to be an essential downstream mediator of EphB4 signaling that occurs during venous adaptation to the arterial environment (Wang et al, 2015). Stimulation of EphB4 with monomeric eph-rinB2/Fc or clustered ephrinB2/Fc resulted in increased eNOS phosphorylation, NO production, and cell migration in vitro; these effects were abolished in the presence of an eNOS inhibitor.…”
Section: Ephb4 and Ephrinb2-associated Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that eNOS is likely to be an essential downstream mediator of EphB4 signaling that occurs during venous adaptation to the arterial environment (Wang et al, 2015). Stimulation of EphB4 with monomeric eph-rinB2/Fc or clustered ephrinB2/Fc resulted in increased eNOS phosphorylation, NO production, and cell migration in vitro; these effects were abolished in the presence of an eNOS inhibitor.…”
Section: Ephb4 and Ephrinb2-associated Signalingmentioning
confidence: 99%
“…These data suggest that EphB4 regulates endothelial cell functions by eNOS phosphorylation. In a mouse vein graft model, loss of EphB4 during vein graft adaptation was associated with increased eNOS activity and adaptive vein graft wall thickening (Wang et al, 2015). …”
Section: Ephb4 and Ephrinb2-associated Signalingmentioning
confidence: 99%
See 2 more Smart Citations